2023
DOI: 10.1021/acs.langmuir.2c03000
|View full text |Cite
|
Sign up to set email alerts
|

Diffusiophoresis and Diffusio-osmosis into a Dead-End Channel: Role of the Concentration-Dependence of Zeta Potential

Abstract: Chemically induced transport methods open up new opportunities for colloidal transport in dead-end channel geometries. Diffusiophoresis, which describes particle movement under an electrolyte concentration gradient, has previously been demonstrated in dead-end channels. The presence of solute concentration gradients in such channels induces particle motion (phoresis) and fluid flow along solid walls (osmosis). The particle velocity inside a dead-end channel is thus influenced by particle diffusiophoresis and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…It was previously observed that the electrolyte concentration inside the dead-end channel can influence the zeta potential of the particles, which further affects the dynamics of the particles. 15,19 Here, we observed stable zeta potential values throughout the experimental range after coating with polyelectrolytes, allowing for experimental investigation with a constant zeta potential of particles. Diffusiophoresis experiments were performed with one bilayer of PDADMAC/PSS-coated particles that were coated at varying salt concentrations during coating.…”
Section: Polyelectrolyte Adsorptionmentioning
confidence: 64%
See 2 more Smart Citations
“…It was previously observed that the electrolyte concentration inside the dead-end channel can influence the zeta potential of the particles, which further affects the dynamics of the particles. 15,19 Here, we observed stable zeta potential values throughout the experimental range after coating with polyelectrolytes, allowing for experimental investigation with a constant zeta potential of particles. Diffusiophoresis experiments were performed with one bilayer of PDADMAC/PSS-coated particles that were coated at varying salt concentrations during coating.…”
Section: Polyelectrolyte Adsorptionmentioning
confidence: 64%
“…For example, theoretical calculations (based on eq ) show that a change of zeta potential from −10 to −55 mV results in approximately an order of magnitude difference in diffusiophoretic velocity for the same NaCl gradient. Previously, we experimentally demonstrated that the change in salt concentrations influences the diffusiophoretic particle mobility, resulting in a deviation between numerical predictions based on constant zeta-potential and experimental results for the case when the particle zeta potential strongly depends on the salt concentration . We were able to achieve good agreement between experiments and simulations by adjusting the zeta potential according to the salt concentration at a given location and time.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…2017; Gupta, Shim & Stone 2020 b ; Alessio et al. 2022; Lee, Lee & Ault 2022; Migacz & Ault 2022; Akdeniz, Wood & Lammertink 2023). For typical solutes with modest zeta potentials, the diffusioosmotic mobility, , can range from approximately to .…”
Section: Modelling Diffusioosmotic Dispersion In a Long Narrow Channelmentioning
confidence: 99%
“…This regime might appear to be difficult to obtain in the absence of fluid flow. However, such a regime is commonly observed in microfluidic experiments with colloidal particles via the process of diffusiophoresis, i.e., transport of colloidal particles in response to solute concentration gradients (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The key feature observed in diffusiophoretic systems is the banding of colloidal particles that creates a region of sharp colloidal concentration gradients (18,21,25,26,(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%